Migraine Aura: Pathophysiology, Mimics, and Treatment Options - Fraser, Clare L.; Hepschke, Jenny L.; Jenkins, Bronwyn; Prasad, Sashank (Seminars in Neurology, 2019)
Recent insights into the clinical presentation and pathophysiology of migraine aura have paved the way for new treatments for this common but frequently debilitating condition. Marked efflux of cellular potassium and glutamate contributes to the cortical spreading depression that forms the electrophysiological basis of migraine aura phenomena. Secondary vascular perturbations also contribute to the various symptoms of a migraine attack. Calcitonin gene-related peptide (CGRP) plays a key role in many of these steps, and a growing class of CGRP-antagonists have emerged as a novel, efficacious preventative therapy. It is still not fully understood why a preponderance of migraine aura symptoms is visual, and this issue is an active area of research. In addition, the pathophysiological changes responsible for visual snow syndrome are under investigation. Before diagnosing a patient with migraine aura, it is important to consider the differential diagnosis of transient visual phenomena, with attention to clinical features that may suggest conditions such as retinal disorders, transient ischemic attack, or occipital epilepsy.
Keywords: migraine; aura; visual snow